Addiction and Mindfulness; Pornography Addiction and Mindfulness-Based Therapy ACT. Issue 1 (3rd April 2019) - Fraumeni-McBride, Julie
Abstract: Mindfulness, more specifically acceptance and commitment therapy (ACT) may be the most optimal form of therapy to be used in treating problematic pornography use—use that may qualify as addiction, which falls within the realm of sex addiction. ACT would be beneficial to apply in a clinical setting for 1-on-1 therapy, coaching and sexuality workshops using the ACT model. Though some ambiguity exists on whether pornography addiction falls within the realm of sex addiction, there is sufficient theoretical framework to apply addiction identifiers to problematic pornography use, which further has implications to the benefits of using ACT in treating perceived problematic or addictive pornography use.